The effect of training and development on the performance of employees in the Limpopo Gambling Board, Limpopo Province - Legodi, Mphengwa John (My University, 2021)
Training and development plays a critical role in ensuring that employees perform better in their daily duties and most of the organizations view training and development as a waste of time and resources. Training and development plays a key role in motivating and inspiring employees in an organization. The study is aimed at analyzing the effect of training and development on the performance of employees in the Limpopo Gambling Board. The study also aimed at investigating whether training and development can promote the performance of the employees in the board. The information was obtained using mainly a questionnaire survey which was circulated to employees in the board. A total of 33 completed questionnaires were received back from the respondents. Additionally, a face-to-face semi structured interview was conducted with the Manager: Human Resources in the board. Data collected was analysed using STATA. The results from the study show that there is no training and development policy in the board. The further reveals that the majority of the respondents at 76.92% are able to implement the knowledge gained during training in their daily duties. This is a clear indication that training and development has a positive effect on the performance on the employees in the board. The study also indicated that employees are not given equal opportunity to attend training and development programmes in the board and this is supported by the majority of respondents at 84.62% who tend to believe that employees are not provided with equal opportunity to attend training and development in the board. The majority of respondents and Manager Humana Resources highlighted budget constraints as the major problem with regard to training and development of employees in the board and therefore there is a need for the board to provide adequate funds to training and development of employees.
Thesis (MPAM.) -- University of Limpopo, 2021
Keywords: Training and development; Employees performance; Limpopo Gambling Board; Limpopo Province; Employees -- Rating of; Performance -- Management; Occupational training; Performance standards